The Girl from Monday - Hartley, Hal; Cawley, Sarah; Sage, Bill; Lloyd, Sabrina; Abracos, Tatiana (The Hal Harley Collection)
Corporate America has become Big Brother, complete with Orwellian doublespeak and a media indistinguishable from its corporate sponsor. Battling this new corporate world order are a ragtag collection of "counterrevolutionaries" who aren't out to overthrow as much as defy the power. Shot in hi-def video and transferred to film with strobing images and video smears not merely intact but embraced, it looks like a fuzzy memory of things to come. It feels that way too. Hartley's soft spot for offbeat romances is trumped by irony and sloganeering dialogue ("We are the revolution because the revolution is good for business"). But when the illusions and poses are stripped away, he gives his lonely narrator an ending worthy of his loss. [www.seattlepi.com]